ANALISIS PERLAKUAN PEMBERIAN MINYAK SUMBAWA TERHADAP PERTUMBUHAN KUMAN Staphylococcus aureus - Gede, Lalu Sri (Jurusan Analis Kesehatan, Poltekkes Kemenkes Mataram, 2016)
Sumbawa Oil is a product of indigenous tribal communities Sumbawa in West Nusa Tenggara (NTB). Sumbawa oil is a traditional medicine that is beneficial to health and endurance. Sumbawa oil has long been used for treatment because it has Multikhasiat against disease. Sumbawa oil contains compounds that are so complex compounds including tannins, bioflavonoids, saponin, lauric acid which has antibacterial activity, antifungal, and antiviral properties. The purpose of this study to determine the inhibitory Sumbawa oil on the growth of Staphylococcus aureus. This research is true experimental sumbawa oil samples from the concentration of 25%, 50%, 75% and 100%, with the diffusion technique of pitting kirby bauer method. The results showed no Sumbawa oil can inhibit the growth of Staphylococcus aureus. Oil Sumbawa do not have the potential to inhibit the growth of Staphylococcus aureus.